Chemical characteristics of chrome spinel in the magnesite-rich rocks from Swat, northwestern Pakistan - Arif, Mohammad (Journal of Himalayan Earth Sciences, 1996)
The magnesite-rich rocks (magnesite ± talc ± quartz ± fuchsite ± tourmaline ± chlorite), which locally host emerald mineralization, contain trace to accessory amounts of disseminated grains as well as small nodular segregations of chrome spinel. The spinel displays unusually high Cr/(CrAl) and low Mg/(Mg+Fe2+) ratios. A detailed investigation reveals that the present chemical characteristics of the chrome spinel are probably the result of modification related to the formation of the host rocks by a low-grade metamorphism in the presence of a CO2 bearing fluid.